Penerapan Model Pembelajaran Inkuiri dalam Meningkatkan Hasil Belajar Ekonomi pada Peserta Didik Tingkat SMA - Nevia Eki Apriliani (THE JOER: Journal Of Education Research, 2021)
Economics learning in high school is focused on empirical phenomena of economic problems that occur in society. This economic material is very complex because it is related to economic developments which are constantly evolving in line with global developments in the world, starting from the microeconomic system to the macroeconomics (international trade). Through the subject of Economics, students are directed to be able to become citizens of Indonesia who are democratic and responsible, as well as citizens of the world who love peace. The SMA/MA Economics subject aims to enable students to have the following abilities: Understand a number of economic concepts to link economic events and problems with everyday life, especially those that occur within the individual, household, community and country environment. Displays a curious attitude towards a number of economic concepts needed to study economics. Form a wise, rational and responsible attitude by possessing knowledge and skills in economics, management and accounting that are beneficial to oneself, the household, the community and the country. Make responsible decisions regarding socio-economic values in a pluralistic society, both on a national and international scale.